Analysis of Factors Affecting Workforce Productivity in the Steel Tower Production Division of PT X - Rizki Agam Syahputra; Riski Arifin; Iing Pamungkas; Arrazy Elba Ridha; Risnadi Irawan; Nova Nova (Jurnal Industri dan Inovasi (INVASI), 2025)
This study analyzes the impact of age, wages, work environment, working hours, and work experience on workforce productivity in the Steel Tower Production Division of PT X using multiple linear regression (SPSS 16). The analysis includes validity, reliability, multicollinearity, heteroscedasticity, and hypothesis testing. Results show no multicollinearity or heteroscedasticity issues. The R² value (0.545) indicates that 54.5% of productivity variance is explained by the independent variables, while 45.5% is influenced by other factors. However, F-test and T-test results indicate that none of the variables significantly affect productivity.This suggests that other factors, such as motivation or job satisfaction, may play a larger role. Future research should explore these aspects to gain deeper insights.